Forage production in tall fescue and kikuyugrass mixed swards subjected to different defoliation strategies - Winter, Fábio L. (2025)
In some temperate climate regions, co-cultivation of warm- and cool-season perennial grass species represents a promising alternative for sustainable food production. However, managing these pastures is challenging, particularly because of intra-annual competition, which can lead to some species suppressing others. This 3-year study investigated the effects of different defoliation strategies on mixed pastures composed of tall fescue (Schedonorus arundinaceum Schreb; Tf) and kikuyugrass (Cenchrus clandestinus Hochst. ex Chiov; Ky). Treatments were factorial combinations (two × two) of pre-grazing canopy heights (15 and 20 cm) and the presence or absence of a single clean-up grazing event during the spring (SCG). Pre-grazing canopy height and SCG significantly influenced annual forage accumulation (p < 0.05), but there was no interaction between them (p > 0.05). Swards managed at 20 cm or subjected to SCG presented a 10% greater forage production (approximately 15,432 kg DM ha−1) than those managed at 15 cm or without SCG (14,067 kg DM ha−1). All the treatments presented higher intra- and inter-annual stability in forage production (<30% coefficient of variation). The greater annual forage accumulation was mostly attributed to increments in Tf leaf area index and Ky tiller population density over the seasons. Our study demonstrated that in a mixed sward of warm- and cool-season perennial grasses, both the pre-grazing canopy height and the presence of an SCG influence year-round forage production by changing their canopy attributes.